Strategi Guru Pendidikan Agama Islam dalam Pembinaan Kepribadian Akhlak Siswa SMP Negeri 2 Dringu Kabupaten Probolinggo - Nonik Kasiari; Devy Habibi Muhammad; Nuryami Nuryami (ISLAMIKA, 2023)
The purpose of this study is to understand the moral development tried by Islamic religious learning educators at SMP Negeri 2 Dringu, Probolinggo Regency,recognize supporting aspects and obstacles to strengthening student ethics at SMP Negeri 2 Dringu, Probolinggo Regency.The method used by the researcher is qualitative, where this method is more of a description, which is intended to describe the information contained in the research position. Procedures for collecting information through observation, interviews and documentation. The analysis of information uses methods of reduction, presentation of information and drawing conclusions. The results of the deepening show thatstrategies for islamic learning educators at SMP Negeri 2 Dringu, Probolinggo Regency, to strengthen student ethics, including mentoring strategies, supervision or monitoring strategies, adjustment strategies, linkages, using reward strategies and supporting aspects as well as barrier aspects to strengthen the morals of students of SMP Negeri 2 Dringu, Probolinggo Regency,The supporting aspect is the school's habit that is suitable for the moral development of students and has a vision, mission and purpose that is in harmony. On the contrary, the barrier aspect is the conflicting background of students, the lack of a balance between the school area, the family area and the residents' area, obstacles arise from the students themselves.